The Forgotten Numbers: A Closer Look at COVID-19 Non-Fatal Valuations - Thomas J. Kniesner; Ryan Sullivan (Institute of Labor Economics (IZA), 2020)
Our research estimates Covid-19 non-fatal economic losses in the U.S. using detailed data on cumulative cases and hospitalizations from January 22, 2020 to July 27, 2020, from the Centers for Disease Control and Prevention (CDC). As of July 27, 2020, the cumulative confirmed number of cases was about 4.2 million with almost 300,000 of them entailing hospitalizations. Due to data collection limitations the confirmed totals reported by the CDC under-count the actual number of cases and hospitalizations in the U.S. Using standard assumptions provided by the CDC, we estimate that as of July 27, 2020, the actual number of cumulative Covid-19 cases in the U.S. is about 47 million with almost 1 million involving hospitalizations. Applying value per statistical life (VSL) and relative severity/injury estimates from the Department of Transportation (DOT), we estimate an overall non-fatal unadjusted valuation of 2.2 trillion for the U.S. with a weighted average value of about 46,000 per case. This is almost 40% higher than the total valuation of 1.6 trillion (using about 11 million VSL from the DOT) for all approximately 147,000 Covid-19 fatalities. We also show a variety of estimates that adjust the non-fatal valuations by the dreaded and uncertainty aspect of Covid-19, age, income, and a factor related to fatality categorization. The adjustments show current overall non-fatal valuations ranging from about 1.5 trillion to about 9.6 trillion. Finally, we use CDC forecast data to estimate non-fatal valuations through November 2020, and find that the overall cumulative valuation increases from about 2.2 trillion to about 5.7 trillion or to about 30 percent of GDP. Because of the larger numbers of cases involved our calculations imply that non-fatal infections are as economically serious in the aggregate as ultimately fatal infections.
Keywords: I18; J17; J28; H51; 330; value of a statistical injury; VSI; value of a statistical life; VSL; COVID-19; pandemic; willingness to pay; benefit-cost analysis; CDC